Estresse ocupacional e qualidade de vida no contexto hospitalar: um estudo psicossociológico - Barros, Iany Cavalcanti da Silva (2013)
This study aimed to investigate the relationship of occupational stress on quality of life of the professionals of administrative and health in hospital settings. To achieve this goal, it was necessary to conduct two studies. The first in order to understand the social representations (RS) on occupational stress and quality of life, developed by these professionals. It was a field research, exploratory character multimethod, with 70 professionals working in three public and private hospitals in the city of João Pessoa, PB, which underwent a sociodemographic questionnaire, the technique of free association of words and interviews -structured. For data processing, we used the SPSS software (version 18), the Tri-Deux-Mots (version 2.0) and Alceste. The majority (50%) were older than 39 years, (64.6%) were female; (57%) fall within the service time 1-5 years. The results from the tri-deux mots showed an advantage of 68.2% on the training plan factorial correspondence. From the four-inducing stimuli (i) occupational stress, (ii) quality of life, (iii) professional practice, and (iv) myself, constituted the semantic fields: (F1) represented by professionals, and (F2) by sex, evidenced objectifications around occupational stress associated with the fight, moodiness and fatigue, quality of life in the elements have salary, welfare and be responsible, professional practice in knowledge, love and growth in myself happy, mother and devoted friend. The results of semi-structured interviews arising from Alceste demonstrated a aprofeitamento of (63%) of the corpus, resulting in four classes: (i) the procedure and practical work (12%), (ii) conflicting relationships (37%), (iii ) dimensions of quality of life (36%), (iv) stressors (15%). From the results of Study 1, it can be inferred that there is consensus and dissent in the social representations of the two groups. The second study aimed to assess the level of occupational stress and quality of life for professionals working in those contexts. The study included 240 professionals, aged 17-74 years (mean = 34.8, SD = 10.16), the majority (64.6%) were female (62.9%) of the Catholic religion, (72.3%) work between 1-10 years. The results from the statistical analyzes showed that participants have a moderate level of stress, emphasizing that the effect of this construct negatively influenced the quality of life. It is concluded that these findings suggest that the relationship of occupational stress on quality of life influences in human actions, and do your work, denoting organic effects, psychological and behavioral attitudes that will trigger, lifestyle behaviors and vulnerability, affecting the health professional in the organizational environment.